Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0056909
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Atmospheric Boundary Layer and Its Significance to the Stratosphere and Troposphere Exchange over the Tibetan Plateau

Abstract: In this study the depth of the atmospheric boundary layer (ABL) over the Tibetan Plateau was measured during a regional radiosonde observation campaign in 2008 and found to be deeper than indicated by previously measurements. Results indicate that during fair weather conditions on winter days, the top of the mixed layers can be up to 5 km above the ground (9.4 km above sea level). Measurements also show that the depth of the ABL is quite distinct for three different periods (winter, monsoon-onset, and monsoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 56 publications
4
76
0
1
Order By: Relevance
“…area to study atmospheric dynamics, and difficult for modelling so it can serve as a test case to see if the dynamics in the model are correctly implemented. On 25 February 2008 a stratosphere-troposphere exchange event was observed in GOME-2 data (Chen et al, 2013), which can also be observed in the assimilation output. In Fig.…”
Section: Case Studysupporting
confidence: 61%
“…area to study atmospheric dynamics, and difficult for modelling so it can serve as a test case to see if the dynamics in the model are correctly implemented. On 25 February 2008 a stratosphere-troposphere exchange event was observed in GOME-2 data (Chen et al, 2013), which can also be observed in the assimilation output. In Fig.…”
Section: Case Studysupporting
confidence: 61%
“…This result strongly suggests that the topography of the Tibetan Plateau can exert an influence on the lower stratosphere and upper troposphere. Škerlak et al (2014) compiled a global 33 yr climatology of STE from 1979 to 2011 and concluded that the Tibetan Plateau is one of the global hot spots for deep STE, where the very high orography combined with a high mixing layer enables quasi-horizontal transport into the Planetary boundary layer (PBL) (Chen et al, 2013 (Tang et al, 1995;Klausen et al, 2003;Wang et al, 2006;Xu et al, 2011) and, on the southern rim, for the Nepal Climate Observatory-Pyramid (NCO-P; 27.95 • N, 86.80 • E; 5079 m a.s.l.) in the Himalaya range (Cristofanelli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Radiosonde observations over the Tibetan Plateau (TP) reveal a high frequency (~80% of all profiles) of multiple thermal tropopauses during winter . Stable potential temperature (hereafter referred to as theta) and low RH over the Tibetan Plateau during winter can potentially enhance the downward transport of O3 rich dry eddies of stratospheric origin as a part of BrewerDobson circulation (Chen et al, 2013;Bracci et al, 2012;Hocking et al, 2007). Model calculations, surface observations, and back trajectories suggest that stratospheric intrusions in the Himalayan region occur most frequently during winter and early spring Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stable potential temperature (hereafter referred to as theta) and low RH over the Tibetan Plateau during winter can potentially enhance the downward transport of O3 rich dry eddies of stratospheric origin as a part of BrewerDobson circulation (Chen et al, 2013;Bracci et al, 2012;Hocking et al, 2007). Model calculations, surface observations, and back trajectories suggest that stratospheric intrusions in the Himalayan region occur most frequently during winter and early spring Chen et al 2013). STE events have also been detected during winter over the Indian plains (Gupta et al, 2007) and at the edge of the Himalayan foothills (Ojha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation